2018
DOI: 10.1186/s12889-018-5024-6
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with HIV positive sero-status among exposed infants attending care at health facilities: a cross sectional study in rural Uganda

Abstract: BackgroundEast and South Africa contributes 59% of all pediatric HIV infections globally. In Uganda, HIV prevalence among HIV exposed infants was estimated at 5.3% in 2014. Understanding the remaining bottlenecks to elimination of mother-to-child transmission (eMTCT) is critical to accelerating efforts towards eMTCT. This study determined factors associated with HIV positive sero-status among exposed infants attending mother-baby care clinics in rural Kasese so as to inform enhancement of interventions to furt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 9 publications
3
13
0
1
Order By: Relevance
“…It is also consistent with the finding from a study by Jamieson et al (2012) (43) which showed that infant Nevirapine for 28 weeks was effective in reducing HIV transmission during breastfeeding (43). According to a report by Kahungu et al (2018) and Fisseha and Bereket (2016), infants who did not receive ART prophylaxis at birth had a five-fold risk of being HIV infected compared to those who received prophylaxis (44,45). Similarly in an…”
Section: Duration Of Breastfeeding and Hiv-free Survivalsupporting
confidence: 88%
“…It is also consistent with the finding from a study by Jamieson et al (2012) (43) which showed that infant Nevirapine for 28 weeks was effective in reducing HIV transmission during breastfeeding (43). According to a report by Kahungu et al (2018) and Fisseha and Bereket (2016), infants who did not receive ART prophylaxis at birth had a five-fold risk of being HIV infected compared to those who received prophylaxis (44,45). Similarly in an…”
Section: Duration Of Breastfeeding and Hiv-free Survivalsupporting
confidence: 88%
“…A total of nine countries and 33 studies were included in this systematic review and meta-analysis. Of this, sixteen studies were from Ethiopia (5-11, 21-24, 26-28, 37, 38 ), five studies were from Kenya [ 12 , 15 , 20 ], three studies were from Tanzania [ 13 , 16 ], three studies were from Uganda [ 14 , 18 , 19 , 31 ], two studies were from Zimbabwe [ 33 , 34 ], and the remaining one study was from Eritrea [ 19 ], South Sudan [ 32 ], Malawi [ 35 ], and Rewanda [ 36 ]. In this review, eighteen studies were cross-sectional study designs while fifteen studies were cohorts (Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…The place of delivery [ 6 , 7 , 10 , 14 , 18 , 21 , 24 , 25 , 27 , 38 , 39 ], mixed feeding [ 6 , 9 , 15 , 21 , 25 , 27 , 39 ], mother’s age [ 5 , 24 ], residence [ 7 , 27 ], time to initiate infant prophylaxis [ 7 – 10 , 27 ], mother’s HIV stage [ 9 , 18 ], antenatal care visits [ 8 , 9 , 18 ], prevention of vertical HIV infection [ 6 , 7 , 24 ], and feeding practices [ 7 , 8 , 24 ] were a number of the factors for acquisitions of HIV infection for exposed infants and children. Of these factors, four factors (place of delivery, duration of mother on ART, initiation of ART prophylaxis for newborns, and mixed feeding) were chosen to work out their effect on vertical HIV infection.…”
Section: Introductionmentioning
confidence: 99%
“…For example, maternal CD4 count during pregnancy, mixed feeding, and being hospitalized since birth were noted among children born to mothers in PMTCT programs in Zimbabwe [36]. A study among HIV exposed children in Uganda observed that infants who did not receive ART prophylaxis at birth and children delivered outside the health facility were more likely to be HIV-positive than their counterparts [37]. Significant association between malnutrition and HIV status in children has been observed in many countries, including Burkina Faso, Ghana, Rwanda, and India [38][39][40][41][42].…”
Section: Gaps In Testing Coverage and Efficacy For Orphans And Vulnermentioning
confidence: 99%